2008
DOI: 10.1093/jac/dkn081
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of antimicrobial-resistant Pseudomonas aeruginosa from sputa of cystic fibrosis patients by culture on selective media

Abstract: For most antimicrobials, selection of colonies from conventional media for antimicrobial susceptibility testing provided a considerable underestimation of resistance in P. aeruginosa. The use of selective media for the culture of whole sputum was effective for the detection of resistant isolates of P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…The author of this study concludes that in agreement with previous studies on the use of aerosolized combination therapy of tobramycin and azlocillin as well as the triple combination of tobramycin plus azlocillin and ticarcillin-clavulanic acid (Timentin), conventional measures of antimicrobial resistance may underestimate the clinical efficacy of tobramycin and colistin when delivered at the high concentrations achieved with the TSI formulation (320)(321)(322). These findings are in agreement with the poor predictability of clinical success by conventional susceptibility testing (31,79,80,(118)(119)(120)(121)(122)(123).…”
Section: Colistinsupporting
confidence: 87%
See 3 more Smart Citations
“…The author of this study concludes that in agreement with previous studies on the use of aerosolized combination therapy of tobramycin and azlocillin as well as the triple combination of tobramycin plus azlocillin and ticarcillin-clavulanic acid (Timentin), conventional measures of antimicrobial resistance may underestimate the clinical efficacy of tobramycin and colistin when delivered at the high concentrations achieved with the TSI formulation (320)(321)(322). These findings are in agreement with the poor predictability of clinical success by conventional susceptibility testing (31,79,80,(118)(119)(120)(121)(122)(123).…”
Section: Colistinsupporting
confidence: 87%
“…Basically, heteroresistance implies that the bacterial population in CF airways is significantly undersampled, resistance rates are underestimated, and there are subpopulations with different MICs. Therefore, routine susceptibility testing is not applicable, as the results are not representative of a heterogeneous population of P. aeruginosa (118). Consequently, data generated by routine methods are poorly predictive; ciprofloxacin susceptibility and resistance of a mixed-morphotype strain of P. aeruginosa from a CF patient were correctly predicted in 87.0% and 41.7% of cases, respectively (119), and another analysis revealed that the conventional approach of susceptibility testing indicated susceptibility in 45% of the isolates studied, although resistant subpopulations were identified by population analysis in all of these samples classified as being susceptible (120).…”
Section: Implications For Susceptibility Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well recognised that the distribution of microorganisms in the CF lung is inhomogeneous. Hence, it is not surprising that, even for a single species, a wide distribution of MICs can exist [36,37].…”
Section: Local Concentrations Of Antibioticsmentioning
confidence: 99%